Prevalence and mean intensity of Anisakis simplex (sensu stricto) in European sea bass (Dicentrarchus labrax) from Northeast Atlantic Ocean - C.E.M. Bernardi; P. Cattaneo; A. Gustinelli; M. L. Fioravanti; M. Caffara; S. Mattiucci (International Journal of Food Microbiology, 2011)
Viscera and muscle of a total of 40 wild 1-2 kg European sea bass (Dicentrarchus labrax) from Northeast Atlantic (FAO area 27) were examined for Anisakidae larvae detection by digestion method. Extracted parasites were counted and mean intensity was calculated. Parasites were identified by genetic/molecular markers (allozymes and sequences analysis of the mtDNA cox2 gene) as belonging to the species Anisakis simplex (sensu stricto). In viscera, the main localisations of the larvae were under the gastric serosa, where several parasites alive and dead were found, and intestinal serosa. The visceral prevalence was 0.950 and the mean intensity was 96.39. The main localisation of A. simplex (s.s.) in edible parts was in belly muscles, with a prevalence of 0.425 and a mean intensity of 1.9. This is the first record on the prevalence and mean intensity of A. simplex (s.s.) in European sea bass muscle. This finding has an important consequence on epidemiology of anisakiasis and public health risk assessment.